A review of the Neotropical genus Alloscolytroproctus Hustache, 1929 (Coleoptera; Curculionidae: Dryophthorinae) - Anderson, Robert S. (Zootaxa, 2008)
The genus Alloscolytroproctus Hustache is reviewed. It includes the type species, A. peruanus Hustache, and two new species, A. dominicae Anderson, sp. n, from the West Indies (Dominica) and A. ashei Anderson, sp. n., from Venezuela. All species are likely associated with palms. A key to the three species is provided, along with illustrations of the species and summaries of their natural history and distribution.